Anaemia and transfusion in nonagenarians undergoing emergency, non‐traumatic surgery: a prospective observational study. Issue 4 (7th February 2013) - Pelavski, A. D.; de Miguel, M.; Lacasta, A.; Rochera, M. I.; Roca, M.
SUMMARY Objectives To characterise transfusion and determine its main predictors in nonagenarians undergoing non‐elective, non‐traumatic surgery. Simultaneously, we compared nonagenarians to a similar, but younger sample, as far as the transfusional policy is concerned. Background Perioperative anaemia and transfusion are currently topical, but little is known about them in this population. Methods In this prospective observational study, we recruited 135 patients older than 90 who underwent a non‐elective, non‐traumatic procedure, between 2006 and 2011. A descriptive statistical analysis was performed and a logistic regression model developed. As a control sample, we used a similar number of patients in their third age (between 65 and 85 years old), who underwent the same procedure, during the same period. Results Thirty‐five per cent of the nonagenarians were transfused. The main independent factors associated with transfusion were anaemia (OR 6·77, P < 0·01), a coexisting neoplasm (OR 10·99, P < 0·01) and the need for an exploratory laparotomy (OR 3·05, P = 0·01). When comparing the nonagenarians to the younger group, we found a significant difference in their basal health status and the mortality rate (P < 0·01), but the transfusion policy did not differ substantially, except for the haemoglobin threshold (P = 0·01). Conclusions The independent transfusion predictors in nonagenarians should be taken into account for cross‐matching. Transfusional policy being similar between nonagenarians and third‐aged patients; the differences in thresholds were due to the differences in the populations.